ACUTE LIVER FAILURE ASSOCIATED WITH HEPATITIS E INFECTION IN A YOUNG MAN WITH IMMUNE THROMBOCYTOPENIA - Radka Komitova; Аni Kevorkyan; Еlitsa Golkocheva-Markova; Мaria Atanasova; Оliana Boykinova (Peytchinski Publishing, 2021)
Autochthonous hepatitis E virus (HEV) infection is an increasingly recognized zoonosis in western countries. It is often asymptomatic but may cause severe illness, particularly in immunocompromised patients or those with underlying chronic liver diseases. Even less frequently, cases of acute failure have been reported. In this article, we describe a case of an immunocompetent patient who presented with symptomatic acute HEV hepatitis and progressed to acute liver failure. The patient was transferred to another hospital for further management and transplant consideration. Unfortunately, he developed multi-organ failure thereafter and died before the transplantation became feasible. Subsequently, HEV was confirmed in archived serum by detection of HEV RNA using commercial RT-PCR. The results of this study have confirmed that HEV testing should be included in the initial evaluation of every acute liver failure regardless of travel history, risk factors or underlying chronic liver diseases. This approach might support clinical decisions and enable to use of potential antiviral therapy.